KAJIAN SOSIOLOGI SASTRA DAN PENDIDIKAN KARAKTER DALAM NOVEL NUN PADA SEBUAH CERMIN KARYA AFIFAH AFRA SERTA RELEVANSINYA DENGAN MATERI AJAR DI SMA - Saddhono, Kundharu; Waluyo, Herman J.; Raharjo, Yusuf Muflikh (Jurnal Pendidikan Indonesia, 2017)
This study aimed to describe the content of the novel Nun: In A Mirror by Afifah Afra in terms of literature sociology. This novel also has a character education materials and relevance to the senior high school teaching material in class 12, 2013. This novel curriculum Nun Tells about the characters and the problems of his life as an actress Ketoprak and economic problems. This study is a qualitative research approach through content analysis of literature study sociology. The results of this study is that the novel Nun: In a Mirror phenomenon shows that close to the community. This novel also provide elements of art and local culture are able to enrich the cultural knowledge of the people, especially for students. Therefore, the content of the novel has the potential to be used as teaching material in high school class 12, according to KD 3.1 and 4.1.